Pricing efficiency of the 3-month KLIBOR futures contracts: An empirical analysis - Razak, Marina Abdul; Bacha, Obiyathulla Ismath (Chapman & Hall, 2009)
This study is an empirical investigation of the pricing efficiency of Malaysia's interest rate futures contract, the 3-month Kuala Lumpur Interbank Offered Rates (KLIBOR) futures contract. This article also examines several issues related to pricing efficiency. The study spans the contract's entire 10-year history, June 1996 to June 2006. In line with findings in other markets, we find a pre-ponderance of overpricing. Almost 80% of the mispricing constituted overpricing of the futures contract. Mean overpricing was 8 basis points. Our results lend support to the hypothesis that there may be a 'Futures Habitat Premium'. Underpricing, though less frequent was of a larger magnitude and had higher volatility. Even after adjusting for brokerage costs, most of the price deviations were arbitrageable. We find the extent of mispricing to be dependent on the trend and volatility of the underlying rate. Analysis of the impact of switch in Central Bank target policy rate, away from the underlying asset of the futures contract, showed higher pricing deviation post switch. Our examination of the interest rate announcement effect showed the spot market to be more responsive and faster in reaction than the futures market. The magnitude of reaction to rate cuts appears to be different at different interest rate levels.